Delivering exceptional project results a practical guide to project selection, scoping, estimation and management - Moustafaev, Jamal (J. Ross Pub., 2011)
Offers a road-map for unifying project and portfolio management into comprehensive and proven framework. This 'how to' implementation guide unifies project management, portfolio management, and requirements engineering into one comprehensive best practice framework to help organizations deliver exceptional project results on a consistent basis